KETERLIBATAN WARGA DALAM PEMBENTUKAN RUANG PUBLIK (ANALISA PEMBENTUKAN RUANG PUBLIK DALAM REVITALISASI PASAR TRADISIONAL DI KOTA SURAKARTA) - Himawan, Adi; Kartono, Drajat Tri; SN, Supriadi (UNIVERSITAS SEBELAS MARET (UNS), 2013)
This research was conducted to offer a democratic practice model in the era of openness, decentralization and direct local head election. It is the model opening communication spaces within our society post-new order era taking into account cultural, economic and political pluralities. A public policy should be based on the public interest. In democratic world, the broad space for idea exchange and argumentation is opened well when the policy will be implemented by the government.This research was taken place in Surakarta. This study belonged to a qualitative one with phenomenological approach. The sample of research consisted of traditional market seller, municipal government and Surakarta people. Technique of analyzing data used was domain analysis.In the currently developing democratic world, every collective decision making in the form of public policy impossibly occurs without featuring the public space schemata having penetrated many social actions and practices. Public space is the one where the citizens can express their opinions, interest, and needs discursively. Traditional market revitalization policy becomes one important policy taken by Surakarta’s Mayor in managing the city he heads.Keywords: Public space, consensus, involvement, democracy